Analisis Kebijakan Dividen Dalam Memoderasi Profitabilitas, Likuiditas, Dan Leverage Terhadap Nilai Perusahaan - Fitrah Shaumi Ulul Albab; Nor Norisanti; R Deni Muhammad Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze and examine the effect of dividend policy in moderating profitability, liquidity, and leverage on firm value in conventional banking sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The research method used is descriptive associative research method with a quantitative approach. The population in this study amounted to 42 companies with a sample of 10 companies with observations for three years. The results showed that Profitability (ROE) had an effect on firm value, while Liquidity (LAR) and Leverage (DAR) had no effect on firm value, and dividend policy was not able to moderate Profitability (ROE), Liquidity (LAR), and Leverage (DAR). to the value of the company. Keywords : Dividend Policy, Profitability, Liquidity, Leverage, Firm Value